The interdisciplinary work between psychologists and teachers: qualitative study of the meaning expressed by technical advisers in education about their experiences as a work team - Baltar De Andrade, María Julia; Carrasco Aguilar, Claudia; Jensen Bofill, Dennis; Villegas Fernández, Cristian; Tapia Rojas, Nidia (Revista de Psicología, 2012)
This qualitative research describes the meanings of the relationship that psychologists and teachers establish as advisers of a technical assistance strategy specialized in education. The methodology included individual interviews and a focus group, and content analysis was performed on the data. It is concluded that the implementation of interdisciplinary work teams is considered as a distinctive characteristic of educational technical advising that reproduces the history of power relations between psychology and education, in which the field of psychology is regarded as a more reflexive knowledge, and pedagogy is seen as a practical one. Even though this generates social distance between both disciplines, work teams declare an advance to more cooperative work forms, in an interdisciplinary way.